Physics and Technology of Thin Films. - Moshfegh, Alireza Zaker (World Scientific Publishing Company, Incorporated, NetLibrary, Incorporated [distributor], 2004)
Thin films science and technology plays an important role in the high-tech industries. Thin film technology has been developed primarily for the need of the integrated circuit industry. The demand for development of smaller and smaller devices with higher speed especially in new generation of integrated circuits requires advanced materials and new processing techniques suitable for future giga scale integration (GSI) technology. In this regard, physics and technology of thin films can play an important role to achieve this goal. The production of thin films for device purposes has been develo.